2011
DOI: 10.1108/19852511111173095
|View full text |Cite
|
Sign up to set email alerts
|

Internal corporate governance and board performance in monitoring roles

Abstract: Purpose -This paper aims to examine the relationship between internal corporate governance mechanisms and board performance in monitoring roles. Design/methodology/approach -A survey questionnaire was used to gather data on board performance, while annual reports were employed to gather data on internal corporate governance mechanisms. Data for board performance were based on 112 directors who represent the companies. Findings -Factor analysis extracted two dimensions of monitoring roles: management oversight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 58 publications
5
49
0
Order By: Relevance
“…The independent variable was adopted 5-point Likert scale ranging from "1=strongly disagree" to "5=strongly agree". Firm complexity (measured by number of business segments, adopted from Gordon et al, (2009), BODs' monitoring (10 items) is adapted from Kamardin & Haron (2011) and firm size (measured by number of employees, adopted from Gordon et al, (2009), are the moderating variables in this study. 5-point Likert scale ranging from "1=strongly disagree" to "5=strongly agree" was utilized in measuring the moderating variables.…”
Section: Methods Of Analysismentioning
confidence: 99%
“…The independent variable was adopted 5-point Likert scale ranging from "1=strongly disagree" to "5=strongly agree". Firm complexity (measured by number of business segments, adopted from Gordon et al, (2009), BODs' monitoring (10 items) is adapted from Kamardin & Haron (2011) and firm size (measured by number of employees, adopted from Gordon et al, (2009), are the moderating variables in this study. 5-point Likert scale ranging from "1=strongly disagree" to "5=strongly agree" was utilized in measuring the moderating variables.…”
Section: Methods Of Analysismentioning
confidence: 99%
“…However, the findings from studies on the effectiveness of outside directors, particularly the effectiveness of the monitoring role of independent directors, are mostly found to be insignificant. Several studies have suggested that having excessive multiple directorships is one of the factors that leads to directors not producing a positive effect on firm performance (Haniffa & Hudaib 2006;Jackling & Johl 2009), management oversight role (Kamardin & Haron 2011a), or the strategic role performed by the directors (Kamardin & Haron 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…Second, we introduce new variables, namely audit committee chairman who is a senior or former audit partner in the audit firm. Third, following the previous studies (Porta, Lopez De Silanes & Shleifer, 1999;Fan & Wong, 2002;Yunos, Smith & Ismail, 2010;Kamardin & Haron, 2011;Abdullah & Nasir (2004); Abdul Rahman & Ali 2006) suggestions of the effect of ownership concentration on monitoring mechanisms, information asymmetry and its impact on earnings quality, we also examine ownership concentration (five largest shareholders) on earnings quality of companies listed on the Malaysian Main Market.…”
mentioning
confidence: 99%